2020
DOI: 10.1186/s12957-020-01856-1
|View full text |Cite
|
Sign up to set email alerts
|

Blood cell count indexes as predictors of anastomotic leakage in elective colorectal surgery: a multicenter study on 1432 patients

Abstract: Background: The aim of this study was to evaluate a series of blood count inflammation indexes in predicting anastomotic leakage (AL) in elective colorectal surgery. Methods: Demographic, pathologic, and clinical data of 1432 consecutive patients submitted to colorectal surgery in eight surgical centers were retrospectively evaluated. The neutrophil to lymphocyte (NLR), derived neutrophil to lymphocyte (dNLR), lymphocyte to monocyte (LMR), and platelet to lymphocyte (PLR) ratios were calculated before surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Consequently, the early prediction of esophageal AL is critical. Most studies show that esophageal AL is related to the increase of NLR on the fourth day after operation (10,11). Our study further confirmed that serum inflammatory indicators, excluding postoperative NLR, are related to esophageal AL and demonstrated that preoperative neutrophil and POD1-3 PLR are associated with esophageal AL.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consequently, the early prediction of esophageal AL is critical. Most studies show that esophageal AL is related to the increase of NLR on the fourth day after operation (10,11). Our study further confirmed that serum inflammatory indicators, excluding postoperative NLR, are related to esophageal AL and demonstrated that preoperative neutrophil and POD1-3 PLR are associated with esophageal AL.…”
Section: Discussionsupporting
confidence: 86%
“…reported that NLR is a useful predictor of AL with an AUC of 0.78 on POD (27). Paliogiannis and colleagues examined 1432 consecutive patients who underwent colorectal surgery and identified that a NLR cutoff value of 7.1 on POD 4 showed the best AUC in predicting AL (0.744; 95% CI: 0.719-0.768) (10). In another study of esophageal AL, mean NLR values demonstrated an increasing trend and were relatively high in the early postoperative period; conversely, a low NLR was associated with a high negative predictive value for AL (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that cancerous tissue would be infiltrated by numerous neutrophils which significantly increased in peripheral blood of cancer patients [ 31 , 32 ]. In the cancer microenvironment, TGF-β signaling can classify neutrophils into N1 and N2 phenotypes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In ammatory markers are routinely measured in patients following colorectal surgery to monitor progress alongside clinical parameters. 1,2 Postoperative C-reactive protein (CRP) levels is particularly useful for the detection of signi cant postoperative complications. [3][4][5] While some physiological derangement is expected following operative intervention, absolute levels of in ammatory markers above expected thresholds, prolonged elevations or a second rise after an initial decline all encourage further investigation or intervention.…”
Section: Introductionmentioning
confidence: 99%